Cinza vegetal como corretivo e fertilizante para os capins marandu e xaraés - Santos, Claudia Cardoso dos (2012)
The vegetable ash appears as an option for owning fertilizer nutrients needed by plants that can optimize the productivity and quality of grasslands. The objective was to evaluate the production characteristics, structural and nutritional Brachiaria brizantha cultivars Marandu and Xaraés in response to doses of vegetable ash. The experiment was conducted in a greenhouse at the Federal University of Mato Grosso, Campus Rondonopolis, MT. In the period from August to December 2011. The completely randomized design, consisting of a 6x2 factorial design, plant gray doses: 0, 3, 6, 9, 12 and 15 g dm-3 and two grasses with six replications. We used pots with a capacity of 7 dm-3 of soil. Soil moisture was maintained by the gravimetric method while maintaining the ability to 60% of maximum capacity. We carried out three sections of the shoots of Brachiaria brizantha at intervals of 30 days. The SPAD readings were taken every 30 days from the seeding of Brachiaria with the use of portable meter of chlorophyll content ClorofiLOG 1030. The structural productive characteristics were evaluated and nutritional: plant height, leaf number, tiller number, leaf dry, culm dry, shoot dry, root dry, relation leaf culm relation of shoot and root dry; SPAD readings, soil pH, efficient use of vegetable ash concentrations of macro and micronutrients in shoots and roots of grasses and Marandu Xaraés. All results were submitted to ANOVA and regression Tukey mean test at 5% probability, using the statistical program Sisvar. Thus, doses of vegetable ash that provided the maximum production of shoots are between 7 and 15 g dm- 3 in the three periods. Considering the whole evaluation period, there was an increase in soil pH units from 4.36 to 6.26. There is a more efficient use of the vegetable ash to produce aerial of grasses evaluated The highest concentrations of macro and micronutrients in shoots and roots of grasses are among Marandu and Xaraés are among vegetable ash levels 4 and12 g dm-3 for evaluated in three cut. However, the vegetable ash has a positive12 influence on the yield characteristics, structural and nutritional grasses and Marandu Xaraés.